Timeliness of Interhospital Patient Transfer (IHT) within Hospital Kluster Perak Utara, Malaysia - Mohammad Miqdam Abdul Aziz; Narwani Hussin; Chng Xiao Yuan; Osman Ali (Asian Journal of Medicine & Health Sciences, 2022)
Background: Interhospital transfer of patients is one of the strategic integrated healthcare delivery systems and involves a series of essential preparation and coordination from both facilities. Research has shown that the emergency department as the gatekeeper to the hospital required continuous quality improvement activities to enhance workflow processes to overcome the ongoing congestion issue. Methods: This study aims to analyse the timeliness of step-up care interfacility patient transfer within Hospital Kluster Perak Utara. A cross-sectional study using data of October, 2019 was used, and a timeline to represent the journey of step-up care of interhospital transfer in the emergency department of Hospital Taiping was analysed. Results: Analysis of the data demonstrated that duration of review time (RTR) (median 70, IQR 70) accounted for a large proportion of time-consuming workflow (59.5%). Factors that increase the overall Interhospital transfer process are multidisciplinary referrals and the requirement to do the emergency department procedure. Total Bed Waiting Time (TBWT) is more extended for the medical ward (median 30, IQR 28). Conclusion: The result indicates that there are potential time-reducing strategies that can be applied and benefited both facilities. Further research is needed to test the quality improvement program that could enhance interhospital patient transfer.